The Mortal Instruments: City of Ashes - Book 2 - Clare, Cassandra (New York : Margaret K. McElderry Books, 2008)
Sixteen-year-old Clary continues trying to make sense of the swiftly changing events and relationships in her life as she becomes further involved with the Shadowhunters and their pursuit of demons and discovers some terrifying truths about her parents, her brother Jace, and her boyfriend Simon.
Keywords: Paranormal fiction; Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Supernatural -- Fiction; Demonology -- Fiction; Magic -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; Young adult fiction